2018
DOI: 10.1186/s12887-018-1222-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and seasonality of common viral respiratory pathogens, including Cytomegalovirus in children, between 0–5 years of age in KwaZulu-Natal, an HIV endemic province in South Africa

Abstract: BackgroundAcute respiratory tract infections contribute significantly to morbidity and mortality among young children in resource-poor countries. However, studies on the viral aetiology of acute respiratory infections, seasonality and the relative contributions of comorbidities such as immune deficiency states to viral respiratory tract infections in children in these countries are limited.MethodsA retrospective analysis of laboratory test results of upper or lower respiratory specimens of children between 0 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
4
14
0
Order By: Relevance
“…In the other hand, most cases occurred before sixmonths of age, particularly for HRV-A infection. Other studies corroborate the same finding such as in western China where the highest HRV infection rate was before six months' age [24] or in South Africa where 60.9% of positive cases were isolated from the same age group [27]. Meanwhile, other studies demonstrated that HRV infection occurs later, between 13 and 36 months [25,28].…”
Section: Discussionsupporting
confidence: 66%
“…In the other hand, most cases occurred before sixmonths of age, particularly for HRV-A infection. Other studies corroborate the same finding such as in western China where the highest HRV infection rate was before six months' age [24] or in South Africa where 60.9% of positive cases were isolated from the same age group [27]. Meanwhile, other studies demonstrated that HRV infection occurs later, between 13 and 36 months [25,28].…”
Section: Discussionsupporting
confidence: 66%
“…A total of 22 papers from 13 countries have reported data on influenza and other respiratory pathogens including both viruses and bacteria 145 167 . From these, 13 studies reported data on respiratory pathogens among children < 5 years with SARI 145 , 146 , 149 , 151 , 153 , 155 , 156 , 161 , 162 , 165 167 , 218 , while 9 studied reported data on respiratory pathogens among other age groups 147 , 148 , 150 , 152 , 157 160 , 163 . The detection of respiratory virus varied considerably.…”
Section: Resultsmentioning
confidence: 99%
“…The continuous invasion and high diversity of rhinoviruses have been observed [ 138 ]. Rhinovirus activity has been detected in countries of all continents: Spain [ 139 ], Brazil [ 140 , 141 , 142 ], Argentina [ 143 ], France [ 125 ], Italy [ 10 , 144 ], the United Kingdom [ 116 ], Russia [ 145 ], Finland [ 146 , 147 ], Canada [ 148 ], the US [ 3 , 102 , 137 , 149 , 150 , 151 ], Australia [ 152 ], Vietnam [ 153 ], China [ 154 , 155 ], Hong Kong [ 156 ], Japan [ 157 ], Burundi [ 158 ], KwaZulu-Natal (a province of South Africa) [ 159 ], Tanzania [ 90 ], and many others, including Antarctica [ 160 ].…”
Section: Epidemiologymentioning
confidence: 99%